The Implementation of Accounting Information System The Selling in PT. Sepuluh Perkasa Bersatu Unggul Sidrap (Accounting Sharia Analysis) - Sarfina; Rusnaena (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2022)
An accounting information system is a system that collects, records, stores, and processes data to produce information for decision making. Accounting information systems can accurately produce financial information and other information obtained from the collection and management of transaction data. Sales are one of the essential activities in the company because the primary source of company income comes from sales. Sales activities can be adequately carried out if supported by an adequate sales system. The purpose of this research is to determine how the sales accounting information system at PT Sepuluh Perkasa Bersatu Unggul is implemented. This research uses descriptive qualitative research with a phenomenological approach. The types and sources of data are primary data and secondary data. methods of data collection using observation, interviews, and documentation. The study's results can be stated as: (1) The accounting system used at PT Sepuluh Perkasa Bersatu Unggul uses a computerized accounting system. The automated system plays a significant role in completing the work of each user, where the automated system can assist in preparing, processing, storing, and generating data according to the needs of system users from each section;(2) the factors influencing the use of sales accounting information systems at PT. Ten Perkasa Bersatu Unggul, which include top management support, personal technical skills, user training and education programs, and end-user satisfaction; (3) The sales accounting information system has been implemented following sharia analysis, namely the principles of responsibility, fairness, and truth in financial reporting and recording transactions measured relatively.